Modifications of the Mathematical Crisher Model for Effective Moduli of Two-Component Elastic Isotropic Composite; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Svetashkov A. A. Aleksandr Andreevich (Numerical Simulation of Physical and Chemical Processes, 2016)
Title screen